Reframing international mindedness: A critical review of its role in international - Mareye, Mohammad (Journal of International Students, 2025)
This review critically examines the concept of international mindedness (IM) within the broader discourse of international education. Drawing on a semi-systematic literature review, the study interrogates how IM has been conceptualized, applied, and critiqued across educational contexts. Adopting a critical lens, the review uncovers the predominantly Western-centric orientation of IM and its implications for educational practices and policy in multicultural and global settings. The findings challenge the assumed universality of the concept and call for a more inclusive and context-sensitive understanding of international mindedness. Thematic sections highlight key trends and tensions in the literature, followed by a discussion of implications for teacher education, curriculum design, and the positioning of international students. The review concludes by advocating for a reimagined, pluralistic approach to IM that reflects the realities of global education.